Baicalin alleviates intestinal inflammation and microbial disturbances by regulating Th17/Treg balance and enhancing Lactobacillus colonization in piglets - Shunfen Zhang; Chengzeng Luo; Kai Li; Junhong Wang; Huixin Wang; Ruqing Zhong; Liang Chen; Qiugang Ma; Hongfu Zhang (Journal of Animal Science and Biotechnology)
Abstract Background Intestinal inflammation is a common and serious health problem in piglet production, especially enteritis caused by pathogenic Escherichia coli (E. coli). This condition often leads to high mortality, slow weight gain, and significant economic losses. Results In this study, we isolated an E. coli strain, SKLAN202302, from the colon of diarrheal piglets to create an intestinal inflammation model for evaluating the protective effects of baicalin. Piglets infected with E. coli exhibited significant reductions in body weight, feed intake, small intestine length, and ileal goblet cell count (P < 0.05), along with deteriorated ileal morphology. However, baicalin supplementation resulted in body weights, feed intake, and intestinal morphology similar to those of the control group. Notably, there was a significant increase in the colonization of Lactobacillus species, particularly Lactobacillus_reuteri, Lactobacillus_amylovorus, and Lactobacillus_johnii, compared to the E. coli group (P < 0.05). At the metabolic and transcriptional levels, E. coli infection increased inflammatory mediators, including eicosanoids (leukotriene F4, prostaglandin F1a, leukotriene E4, thromboxane B2, prostaglandin G2, and PGH2), monosaccharides, and TCA cycle intermediates (oxoglutaric acid, glutaric acid, adipic acid, citric acid, and isocitric acid) in the ileum. It also promoted the expression of genes related to autoimmune diseases and the Th17 differentiation signaling pathway (CTLA4, IFN-ALPHA-8, IL12RB2, TRAV3, TRAV16, FOS, and VEGFA), as well as inflammatory factors. Conversely, baicalin supplementation not only counteracted these effects but also enhanced the presence of metabolites such as phospholipids [including lysoPC (P-18:1(9Z)/0:0), PC (17:0/0:0), lysoPC (16:1(9Z)/0:0), PC (18:0/0:0), lysoPC (18:0/0:0), PA (10:0/i-16:0), and PA (10:0/8:0)] and amino acids. It also regulated genes within the IL-17 signaling pathway (IL4, CCL17, CXCL10, IFNG, and CXCL2), suggesting a mechanism by which baicalin mitigates E. coli-induced intestinal and microbial disturbances. Subsequent flow cytometry analysis showed that E. coli infection increased the numbers of CD3+ and Foxp3+ cells, decreased IL-17A+ cells, and reduced Th17/Treg ratios. Baicalin supplementation restored these parameters to control levels. Conclusions Baicalin supplementation effectively alleviates E. coli-induced intestinal inflammation and microbial disturbances in piglets by enhancing beneficial Lactobacillus colonization, counteracting inflammatory mediators, and regulating immune-related gene expression and the Th17/Treg balance. These findings highlight baicalin’s potential in alleviating intestinal inflammation. Graphical abstract